2016
DOI: 10.1155/2016/5360361
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polydopamine Functionalized Reduced Graphene Oxide-Palladium Nanocomposite for Laccase Based Biosensor

Abstract: Graphene based 2D nanomaterials have attracted increasing attention in biosensing application due to the outstanding physicochemical properties of graphene. In this work, palladium nanoparticles (Pd) loaded reduced graphene oxide (rGO) hybrid (rGO-Pd) was synthesized through a facile method. Laccase (Lac) was immobilized on rGO-Pd by utilizing the self-polymerization of dopamine, which generated polydopamine (PDA). The PDA-Lac-rGO-Pd nanocomposites were further modified on electrode surface to construct novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…The successful linkage of AF to PDA nanospheres was also verified by FTIR measurements (Figure C). As a feature of small molecules, the spectrum for the monomer DA showed narrow peaks, similar to that reported in literature studies. , The bands in 2747, 2634, 2534, and 2433 cm –1 were ascribed to N–H stretching vibration . After polymerization to form PDA, some strong absorption at 1500 cm –1 (NH 2 scissoring vibration), 1342 cm –1 (CH 2 bending vibration), 1320 cm –1 (C–O–H asymmetry bending vibration), 1192 cm –1 (C–O symmetry vibration), and 1178 cm –1 (C–C stretching vibration) significantly decreased because an intramolecular cyclization reaction of DA occurred to generate DHI and its derivatives during the polymerization process. , Moreover, the AF modification did not elevate the absorption around 1500 cm –1 (NH 2 scissoring vibration) because the −NH 2 group of AF was involved in the reaction with PDA nanospheres.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The successful linkage of AF to PDA nanospheres was also verified by FTIR measurements (Figure C). As a feature of small molecules, the spectrum for the monomer DA showed narrow peaks, similar to that reported in literature studies. , The bands in 2747, 2634, 2534, and 2433 cm –1 were ascribed to N–H stretching vibration . After polymerization to form PDA, some strong absorption at 1500 cm –1 (NH 2 scissoring vibration), 1342 cm –1 (CH 2 bending vibration), 1320 cm –1 (C–O–H asymmetry bending vibration), 1192 cm –1 (C–O symmetry vibration), and 1178 cm –1 (C–C stretching vibration) significantly decreased because an intramolecular cyclization reaction of DA occurred to generate DHI and its derivatives during the polymerization process. , Moreover, the AF modification did not elevate the absorption around 1500 cm –1 (NH 2 scissoring vibration) because the −NH 2 group of AF was involved in the reaction with PDA nanospheres.…”
Section: Resultssupporting
confidence: 85%
“…As a feature of small molecules, the spectrum for the monomer DA showed narrow peaks, similar to that reported in literature studies. 24,25 The bands in 2747, 2634, 2534, and 2433 cm −1 were ascribed to N−H stretching vibration. 26 After polymerization to form PDA, some strong absorption at 1500 cm −1 (NH 2 scissoring vibration), 1342 cm −1 (CH 2 bending vibration), 1320 cm −1 (C−O−H asymmetry bending vibration), 1192 cm −1 (C−O symmetry vibration), and 1178 cm −1 (C−C stretching vibration) significantly decreased because an intramolecular cyclization reaction of DA occurred to generate DHI and its derivatives during the polymerization process.…”
Section: Resultsmentioning
confidence: 99%
“…It mostly contains biomolecules on an electrode that interact with analytes and lead to the generation of electrochemical signals [142]. Li et al [90] fabricated a PDA-Lac-rGO-Pd composite for use as a sensing material. An electrochemical biosensor was prepared using composite to detect catechol.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [90] fabricated a composite material for biosensor electrodes through a facile method. The GO was produced from graphite and reduced to rGO using NaOH (Hummers’ method) [91].…”
Section: Methodsmentioning
confidence: 99%
“…The suggested biosensor demonstrated a strong selectivity for one-base mismatch DNA. Furthermore, Li et al [ 18 ] used pDA-Lac-rGO-Pd nanocomposites to create a laccase-based biosensor with great stability, selectivity, and repeatability, as well as exceptional electrocatalytic capability toward phenolic contaminants. Additionally, Bueno et al reported various impedimetric immunosensors for the detection of various biomarkers and pathogens [ 19 ].…”
Section: Introductionmentioning
confidence: 99%